Prevalence of anxiety and depression among physiotherapy students of private institutes in Faisalabad - Umer Shabbir; Wassam Tanveer; Rameeza Warraich; Saad Iftikhar; M Umer Afzal; M Azan (Archives of Depression and Anxiety - Peertechz Publications, 2022)
Objective: The objective of this study was to determine the prevalence, incidence, and related variables of anxiety and depressive disorders among physical therapy students in Faisalabad's private institutes. Material and methodology: This is a cross-sectional study including medical students from the University of Faisalabad's Department of Physical Therapy. Using convenient sampling, 98 subjects were enrolled in the study after the ethics committee approved it. Questions about socio-demographic characteristics like gender, age, and parental education were included in the data collection tool. Descriptive results are represented in the form of Mean ± S.D. Chi-square test was applied for comparison of anxiety and depression with other variables. Checked significance at p-value 0.05. Results: Out of 98 participants, 63(64%) were male and 35(36%) were female. Out of 98 participants, 31(31.36%) were in age group pf 18-22 years, 39(39.79%) were in age group of 23-26 years and 28(27.57%) were in age group of 27-30 year. Average of age was 25.22 ± 2.19 years. Semester wise students included in the study out of 98 26.53% belonged to 2nd semester. 32.65% belonged to 4th semester and 40.85% belonged to 6th semester. After checking the association between variables and anxiety and depression significant difference were found between all variables with p-values less than 0.05. Conclusion: The study discovered high discomfort among physical therapy students. Furthermore, no significant gender variations in the incidence of anxiety and depression were found. Anxiety and depression have a significant societal and individual cost, including failure in clinical and written exams, medical dropouts, professionalism and personality development.